Pengalaman Pengguna Ome Tv Di Kalangan Remaja (Studi Fenomenologi Di SMPN 20 Kota Bengkulu) - Fristy Reka Oktaviani; Anis Endang; Vethy Octaviani (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research was conducted to find out what the experience of Ome TV users is among teenagers, especially students at SMPN 20 Bengkulu City. This research uses descriptive qualitative research methods. Data collection was carried out through interviews, observation and documentation. The technique for taking research informants uses Purposive Sampling. The results of the research show that the experience of Ome TV users among teenagers, especially students at SMPN 20 Bengkulu City, occurs in two phases, namely: Because of Motives or past motives, namely at this stage the students use the Ome TV Application because they have a high sense of fun and curiosity. try several interesting features such as random videos to chats and In Order Motive or future motifs, namely at this stage the student uses the Ome TV application as a place to express themselves, develop English language skills and increase relations or acquaintances to invite them to play online games. . In this research, it turns out that there are many things that can improve their abilities, including developing English language skills, they are more creative and they also find friends who share their hobby in playing online games. Behind this, the author also found negative things from the impact of using the Ome TV application on students at SMPN 20 Bengkulu City, such as a lack of socializing with their classmates and finding random vulgar videos through the Ome TV application media.